Experimental study of ceramic coatings on lower-density ceramic substrates - Torres, Camila Irene (2023)
Adhesion and homogeneity of the coating-substrate were analyzed on the basis of the establishment of coating mineralogy. Substrate raw materials used were kaolin clay and a calcined alumina 4 μm; a series of higher density ceramic coatings were deposited using calcined aluminas 0.5 μm and 4 μm, silica fume, and talc. The dip coating technique was applied to all substrates and later sintered at 1300°C. Shrinkage and density of coatings mixtures and substrate were separately evaluated. X-ray diffraction was utilized to identify the crystalline phases present in the coatings, while optical and electron microscopy were employed for the structural characterization of the coatings. Coatings exhibited lower shrinkage compared to the substrate. Among the specimens that exhibited good adhesion, cracks were observed to extend parallel to the substrate surface. The presence of cristobalite on the coating indicated that the failure mechanism involved buckling. The crack dimension presented on the coating decreased after adding talc to the mixture.